Corrosion mechanisms of Zn(Mg, Al) coated steel in accelerated tests and natural exposure: 1. The role of electrolyte composition in the nature of corrosion products and relative corrosion rate. (January 2015) - Salgueiro Azevedo, M.; Allély, C.; Ogle, K.; Volovitch, P.
Graphical abstract: Highlights: New electrolyte (RW) is used to understand corrosion mechanisms of ZnMgAl. Corrosion mechanisms in tests with NaCl and RW electrolytes are different. Relative corrosion rates of coatings in tests with RW and field exposure are close. Corrosion products formed after tests in RW and in field exposures are similar. NH4 + and HCO3 − are responsible for the difference in corrosion mechanisms. Abstract: The corrosion rates and the nature of the corrosion products on Zn, ZnAl and ZnMgAl coatings on steel are determined for field exposures and for accelerated tests using different electrolytes. A new test electrolyte is proposed, containing NH4 + and HCO3 −, which shows an improved correlation with field exposure in particular respecting the relative corrosion rates and the absence or at least delayed formation of layered double hydroxides. The effect of pH buffering by NH4 + /HCO3 − mixture on the difference in corrosion mechanisms of ZnMgAl coating in accelerated tests using a "standard" NaCl and using the new electrolyte is discussed.